1992
DOI: 10.1017/s0950268800049499
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter enteritis in Saudi Arabia

Abstract: SUMMARYA 12-month survey on the incidence of campylobacter infection in 1217 patients with diarrhoea was carried out in Jeddah, Saudi Arabia. Campylobacters were isolated from 55 (45%) patients, second in prevalence to salmonellas (62 %).Shigellas were isolated from 4-2 % of patients. Campylobacter isolation rates were high in children of all ages, as well as in young adults (36-5 % of all isolates were from adults aged 20-39 years). Isolation rates peaked in September and November. Analysis of the results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…Campylobacter enteritis has been recognized as a public health concern for more than 10 years (2,19). Mainly Campylobacter jejuni and Campylobacter coli have been found in stool samples of children and adults in developing and developed countries, being about as responsible for bacterial diarrhea as Salmonella, Shigella, and Yersinia species (3,4,21). Moreover, recent data confirm the suggested involvement of C. jejuni and C. coli serotypes in Guillain-Barre syndrome (8,10).…”
mentioning
confidence: 91%
“…Campylobacter enteritis has been recognized as a public health concern for more than 10 years (2,19). Mainly Campylobacter jejuni and Campylobacter coli have been found in stool samples of children and adults in developing and developed countries, being about as responsible for bacterial diarrhea as Salmonella, Shigella, and Yersinia species (3,4,21). Moreover, recent data confirm the suggested involvement of C. jejuni and C. coli serotypes in Guillain-Barre syndrome (8,10).…”
mentioning
confidence: 91%
“…Though it is to be noted that a majority of all diarrheal patients in the current study were between 11 and 20 years old, other studies have shown that symptomatic infection mainly affects children younger than 5 years, particularly in developing countries such as Bangladesh, Thailand, Egypt and Nigeria [9] , other researches have shown that Campylobacter enteritis can occur in adults as well as children [9] . A study in Saudi Arabia has shown Campylobacter enteritis to be an important cause of bacterial enteritis both in adults as well as in children [10] .…”
Section: Discussionmentioning
confidence: 99%
“…In all reports from the region, Campylobacter ranked among the top three aetiological agents of bacterial enteritis. In Jeddah, Saudi Arabia, Campylobacter infection was found to be second in prevalence to Salmonella with 69% of these infections being due to C. jejuni and 31% due to C. coli [19]. However, in data from Kuwait, Campylobacter ranked third after Salmonella and enterotoxigenic E. coli [21].…”
Section: Epidemiologymentioning
confidence: 98%
“…A diversity in the occurrence of Campylobacter as an aetiological agent of bacterial enteritis is evident in reports from Saudi Arabia. Three studies reported in the 1990s have reported Campylobacter detection in patients with bacterial enteritis ranging from 2% [18], 4.5% [19] and 28% [13]. In Kuwait the reported data of Campylobacter enteritis was 2.2% in 1981and 7% in 1989 [15].…”
Section: Epidemiologymentioning
confidence: 98%
See 1 more Smart Citation